Analisis Penyebab tidak Ditemukannya Dokumen Rekam Medik Bagian Riset RSUPN dr. Cipto Mangunkusumo Jakarta - Widiyanto Widiyanto; Gamasiano Alfiansyah; Demiawan Rachmatta Putro Mudiono (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Provision of medical record documents in the medical record research center Dr. Hospital CiptoMangunkusumo is still not in accordance with the number of requests needed, in October there were 4,836requests, 3,953 documents were available, in November there were 3,823 requests and 2,977 documentswere available, in December there were 4,151 requests and 3,143 documents were available. The purpose ofthis study was to analyze the absence of medical record documents in the research section. This type ofresearch is a qualitative study using interview, observation and documentation data collection techniquesinvolving 3 respondents. The results of the study showed that the cause of the absence of medical recorddocuments was that the officers' knowledge was still low, the attitude of the officers who were still lacking indiscipline, supporting facilities and infrastructure were lacking and there was no motivation. Improvementefforts to overcome these problems are providing training, disciplinary officers need to be improved, do systemdesign, provide awards and conduct monitoring and evaluation.